2007
DOI: 10.1016/j.jcrs.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humor penetration of gatifloxacin and moxifloxacin eyedrops given by different methods before cataract surgery

Abstract: Moxifloxacin penetrated the aqueous humor better than gatifloxacin regardless of the method of administration. Both antibiotics penetrated the aqueous humor well when given in drop form. They reached and exceeded the minimum inhibitory concentration levels for the most common ocular pathogens causing endophthalmitis. Only moxifloxacin reached these levels when the wick was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 7 publications
(3 reference statements)
0
23
1
1
Order By: Relevance
“…Figure 1 shows the mean concentrations with 2 different volumes of the antibiotic agents in the dilating mixture. Statistical analysis by univariate analysis of variance gave an F (1,96) value of 62.2 for the type of antibiotic agent (P!.001) and an F (1,96) value of 4.2 for the type of procedure (P!.05). Further statistical analysis of each antibiotic agent independently using the MannWhitney U test to control for non-normal distribution of the data showed that the penetration of moxifloxacin into the aqueous humor increased significantly when the volume of the antibiotic in the dilating mixture in which the wick was soaked was doubled (U Z 217.5, P!.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the mean concentrations with 2 different volumes of the antibiotic agents in the dilating mixture. Statistical analysis by univariate analysis of variance gave an F (1,96) value of 62.2 for the type of antibiotic agent (P!.001) and an F (1,96) value of 4.2 for the type of procedure (P!.05). Further statistical analysis of each antibiotic agent independently using the MannWhitney U test to control for non-normal distribution of the data showed that the penetration of moxifloxacin into the aqueous humor increased significantly when the volume of the antibiotic in the dilating mixture in which the wick was soaked was doubled (U Z 217.5, P!.05).…”
Section: Resultsmentioning
confidence: 99%
“…This is because they have a wide spectrum of activity and penetrate well into the eye and there is a low risk for resistance developing against them. A recent study 1 found that the penetration of these antibiotic agents into the aqueous humor was less when they were given in a wick instead of drops before cataract surgery. This present study was performed to determine whether increasing the concentration of the antibiotic agent in the dilating mixture in which the wick is soaked affects its penetration into the aqueous humor.…”
mentioning
confidence: 99%
“…Literature in support of the use of topical preoperative prophylaxis have shown a reduction in the number of ocular surface flora [18,19], and achievement of therapeutic intraocular concentrations of antibiotics, especially newer fourth-generation fluoroquinolones such as moxifloxacin and gatifloxacin [20,21]. Nevertheless, in Singapore, a variety of topical preoperative antibiotics were used, including tobramycin, a bactericidal aminoglycoside, the bacteriostatic chloramphenicol, and levofloxacin and moxifloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…for linezolid (with quantitation limits generally above 0.1 g/ml) [7,[9][10][11][12][13][14]; for the fluoroquinolones moxifloxacin [15][16][17][18][19][20][21][22] and gatifloxacin [23][24][25][26][27] (some of the methods with quantitation limits approaching 0.01-0.02 g/ml, but others much less sensitive); and for the ␤-lactam, cefuroxime (with one exception [28], all having quantitation limits of 0.1 g/ml or higher) [29][30][31]. Other analytical methods have also been utilized for these antibiotics, including liquid chromatography coupled to mass spectrometry (LC-MS) [32][33][34][35][36], capillary electrophoresis (CE) [37][38][39][40][41], capillary electrochromatography (CEC) [42,43], and spectrophotometry [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%